Efficacy of pre- and postinoculation application of Fungicides to expanding young citrus leaves for control of melanose, scab, and alternarial brown spot - Mondal, S. N.; Vicent, A.; Reis, R. F.; Timmer, L. W. (Amer Phytopathological Soc, 2007)
In greenhouse trials, copper hydroxide, pyraclostrobin, and famoxadone were applied to actively crowing young citrus seedlings to determine the duration of protection of young leaves provided by these fungicides against melanose, caused by Diaporthe citri, citrus scab, caused by Elsinoe fawcettii, and Alternaria brown spot, caused by Alternaria alternata. Fungicides were applied to different sets of potted plants of grapefruit for control of melanose, of rough lemon for control of scab, and of Dancy tangerine for control of Afternaria brown spot 1 to 6 days prior to inoculation. as well as on the day of inoculation. Leaf area of treated shoots was estimated on the day of fungicide application and the day of inoculation and disease severity evaluated subsequently. In most cases. copper hydroxide and famoxadone provided at least 50% control of all three diseases for only about 2 days after application. Generally, there was little or no disease control when the products were applied 4 or more days before inoculation. In contrast, pyraclostrobin usually provided a high level of control of all three diseases when applied up to 5 days prior to inoculation. The level of disease control decreased as the interval between a fungicide application and inoculation increased and the relationship between disease control and leaf expansion best fit a quadratic equation. Effective disease control was observed with copper hydroxide and famoxadone until leaf area had increased by 100 to 200%, whereas control with pyraclostrobin was observed up to 400 to 500% increase in leaf area. In postinoculation tests with scab and melanose, pyraclostrobin provided high levels of disease control (>75%) when applied up to 2 days after inoculation. whereas copper hydroxide and famoxadone had minimal postinoculation activity. Applications of pyraclostrobin to the spring flush growth of citrus trees are much more likely to provide control of melanose, scab, and Alternaria brown spot than those of famoxadone or copper hydroxide.